3D-cultured human placenta-derived mesenchymal stem cell spheroids enhance ovary function by inducing folliculogenesis. Issue 1 (December 2018) - Kim, Tae-Hee; Choi, Jong; Jun, Yesl; Lim, Seung; Park, Sohae; Paek, Jin-Young; Lee, Sang-Hoon; Hwang, Ji-Young; Kim, Gi
Abstract Placenta-derived mesenchymal stem cells (PD-MSCs) have numerous advantages over other adult MSCs that make them an attractive cell source for regenerative medicine. Here, we demonstrate the therapeutic effect of PD-MSCs in ovariectomized (Ovx) rats and compare their efficacy when generated via a conventional monolayer culture system (2D, naïve) and a spheroid culture system (3D, spheroid). PD-MSC transplantation significantly increased the estradiol level in Ovx rats compared with the non-transplantation (NTx) group. In particular, the estradiol level in the Spheroid group was significantly higher than that in the Naïve group at 2 weeks. Spheroid PD-MSCs exhibited a significantly higher efficiency of engraftment onto ovarian tissues at 2 weeks. The mRNA and protein expression levels of Nanos3, Nobox, and Lhx8 were also significantly increased in the Spheroid group compared with those in the NTx group at 1 and 2 weeks. These results suggest that PD-MSC transplantation can restore ovarian function in Ovx rats by increasing estrogen production and enhancing folliculogenesis-related gene expression levels and further indicate that spheroid-cultured PD-MSCs have enhanced therapeutic potential via increased engraftment efficiency. These findings improve our understanding of stem-cell-based therapies for reproductive systems and may suggest new avenues for developing efficient therapies using 3D cultivation systems.